Utilization of 1-GHz VCSEL for 11.1-Gbps OFDM VLC Wireless Communication - I-Cheng Lu; Chien-Hung Yeh; Dar-Zu Hsu; Chi-Wai Chow (IEEE Photonics Journal)
In this paper, we propose using an energy-efficient and low-cost 682-nm vertical-cavity surface-emitting laser (VCSEL) with 1-GHz modulation bandwidth for high-speed wireless visible light communication (VLC). Moreover, by using spectral-efficient orthogonal frequency division multiplexing (OFDM) modulation with bit-and-power-loading algorithm, we successfully demonstrate VCSEL-based transmission at 11.1 Gbps (10.2 Gbps in a raw data rate) over a free-space length of 1.2 m under small bias current of 3.5 mA. Furthermore, decreasing the bias current as low as 2 mA, we can also demonstrate 10.5 Gbps (9.7 Gbps in a raw data rate) OFDM VLC transmission over a 1.2-m free-space link. This proposed VCSEL-based OFDM transmission system could be viewed as a cost-effective and energy-efficient approach for high-speed (> 10 Gbps) laser diode wireless VLC application.